Solubility, Hansen Solubility Parameters and Thermodynamic Behavior of Emtricitabine in Various (Polyethylene Glycol-400 + Water) Mixtures: Computational Modeling and Thermodynamics - Faiyaz Shakeel; Nazrul Haq; Ibrahim A. Alsarra; Sultan Alshehri (Molecules, 2020)
This study was aimed to find out the solubility, thermodynamic behavior, Hansen solubility parameters and molecular interactions of an antiviral drug emtricitabine (ECT) in various “[polyethylene glycol-400 (PEG-400) + water]” mixtures. The solubility of ECT in mole fraction was determined at “T = 298.2 to 318.2 K” and “p = 0.1 MPa” using an isothermal method. The experimental solubilities of ECT in mole fraction were validated and correlated using various computational models which includes “Van’t Hoff, Apelblat, Yalkowsky-Roseman, Jouyban-Acree and Jouyban-Acree-Van’t Hoff models”. All the models performed well in terms of model correlation. The solubility of ECT was increased with the raise in temperature in all “PEG-400 + water” mixtures studied. The highest and lowest solubility values of ECT were found in pure PEG-400 (1.45 × 10−1) at “T = 318.2 K” and pure water (7.95 × 10−3) at “T = 298.2 K”, respectively. The quantitative values of activity coefficients indicated higher interactions at molecular level in ECT and PEG-400 combination compared with ECT and water combination. “Apparent thermodynamic analysis” showed an “endothermic and entropy-driven dissolution” of ECT in all “PEG-400 + water” combinations studied. The solvation nature of ECT was found an “enthalpy-driven” in each “PEG-400 + water” mixture studied.